2013
DOI: 10.1002/chem.201204303
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Biological Evaluation of (+)‐Gambieric Acid A and Its Analogues

Abstract: In this study, we report the first total synthesis and complete stereostructure of gambieric acid A, a potent antifungal polycyclic ether metabolite, in detail. The A/B-ring exocyclic enol ether 32 was prepared through a Suzuki-Miyaura coupling of the B-ring vinyl iodide 18 and the alkylborate 33 and subsequent closure of the A-ring by using diastereoselective bromoetherification as the key transformation. Suzuki-Miyaura coupling of 32 with acetate-derived enol phosphate 49, followed by ring-closing metathesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 134 publications
0
17
0
Order By: Relevance
“…We chose to convert iodide 15 to its corresponding borinate using the “ B ‐OMe‐9‐BBN” variation . The borinate can be conveniently prepared by addition of tert ‐butyl lithium to a premixed solution of 15 and B ‐OMe‐9‐BBN (1 m in hexanes) in tetrahydrofuran at −78 °C . We found that the use of Buchwald ’s Pd SPhos precatalyst system (5 mol % SPhos Pd G2, 5 mol % SPhos, Cs 2 CO 3 , THF, DMF, H 2 O, 40 °C) was crucial to obtain high yields, short reaction times (typically around 1 h) and to efficiently suppress unwanted β‐hydride elimination .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to convert iodide 15 to its corresponding borinate using the “ B ‐OMe‐9‐BBN” variation . The borinate can be conveniently prepared by addition of tert ‐butyl lithium to a premixed solution of 15 and B ‐OMe‐9‐BBN (1 m in hexanes) in tetrahydrofuran at −78 °C . We found that the use of Buchwald ’s Pd SPhos precatalyst system (5 mol % SPhos Pd G2, 5 mol % SPhos, Cs 2 CO 3 , THF, DMF, H 2 O, 40 °C) was crucial to obtain high yields, short reaction times (typically around 1 h) and to efficiently suppress unwanted β‐hydride elimination .…”
Section: Resultsmentioning
confidence: 99%
“…[14] The borinate can be conveniently prepared by addition of tert-butyl lithium to ap remixed solution of 15 and B-OMe-9-BBN (1 m in hexanes) in tetrahydrofuran at À78 8C. [15] We found that the use of Buchwald 's Pd SPhos precatalysts ystem (5 mol %S Phos Pd G2, 5mol %S Phos, Cs 2 CO 3 , THF,D MF,H 2 O, 40 8C) was crucial to obtain high yields, short reaction times (typically around1h) and to efficiently suppress unwanted b-hydride elimination. [16] The generalityo ft hese optimizedc onditions was also demonstrated for as mall array of bromoenol ethers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of convergent RCM substrate synthesis by Suzuki coupling with an unsaturated ester-derived enol phosphate, seen earlier in a 2,3-DHF approach towards okadaic acid (61) (Scheme 16), has also been applied in 3,4-DHP synthesis towards the attenol marine toxins (e.g., (−)-attenol A (156), Scheme 47), 59 and the D-ring of (+)-gambieric acid A (157) in the latter's first total synthesis (Scheme 48, NAP = 2-napthylmethyl), 60 and (+)-neopeltolide and analogues. 61 A popular route to 3,4-DHPs 151 from unsaturated esters 158 uses a reduced titanium alkylidene, derived from TiCl 4 and a 1,1-dibromoalkane (Takai-Utimoto reagent, Scheme 49).…”
Section: 4-dihydro-2h-pyransmentioning
confidence: 99%
“…We have recently completed the first total synthesis of GAA to establish its absolute configuration as that shown by 1 (Fuwa et al, 2012 ; Ishigai et al, 2013 ; Sasaki and Fuwa, 2014 ). Our synthesis entailed convergent assembly of the A/BCD- and F′GHIJ-ring fragments, i.e., 2 and 3 , respectively, by means of Suzuki–Miyaura coupling (Miyaura and Suzuki, 1995 ; Sasaki and Fuwa, 2008 ; Suzuki, 2011 ) to give the endocyclic enol ether 4 , followed by closure of the E- and F-rings via a stereoselective allylation of a thioacetal (Suga et al, 2014 ) and a ring-closing metathesis (Hoveyda and Zhugralin, 2007 ), respectively, to construct the nonacyclic polyether core 5 (Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%